Pengaruh Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry)Terhadap Motivasi Belajar dan Keaktifan Siswa Kelas Viii di Dusun Jerneng Lombok Tengah - Eni Apriani; Mukminah Mukminah (Pusat Riset dan Inovasi Nasional, 2024)
The background is based on conditions during the teaching and learning process, teachers still apply lecture, question and answer and discussion methods so that teachers appear more active. Furthermore, the impact of Covid-19 requires online learning, which causes a lack of enthusiasm for students to participate in learning. This research aims to determine the effect of the guided inquiry learning model on the learning motivation and activity of class VIII students in Jerneg Hamlet. The research method used is Quasi experiment with a quantitative approach. The population in this study were all junior high school students in class VIII in Jerneng Hamlet. Sampling used an incidental technique with a total of 20 students, 10 students for the experimental class and 10 students for the control class. The data in this study was taken by giving a pretest and posttest to each class. The data collection technique for the learning motivation variable uses a 20-item questionnaire. Meanwhile, the data collection technique for student activity uses a 15-item questionnaire. Data collection techniques by providing questionnaires, observation sheets and documentation. Data analysis uses Validity Test, Reliability Test, Normality Test, Homogeneity Test and T Test. Based on the results of hypothesis testing on the guided inquiry learning model on student learning motivation, it shows that F = 3.825; sig<0.05. Meanwhile, the results of hypothesis testing on student activity show that F = 1.974; sig<0.05. Based on the results above, it can be concluded that there is an influence of the guided inquiry learning model on the learning motivation and activity of class VIII students in Jerneng Hamlet.